PENGARUH PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KEANDALAN LAPORAN KEUANGAN PADA BANK UMKM JAWA TIMUR - Anjani, Silvia Dwi; Hariyanto, Sugeng (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTWith the application of Good Corporate Governance based on the principles of transparency, independence, accountability, responsibility and fairness, it is expected to create effective internal incentives for company management so that the company's financial statements can be said to be reliable, to be valuable in the global capital market, the information must be clear, consistent and can be compared and use accounting standards that are accepted throughout the world. The population in this study were employees of the East Java Micro, Small and Medium Enterprises, while the sample of this study amounted to 30 respondents. The data used are primary data collected through questionnaires. The method used to test hypotheses is simple linear regression analysis. The results of this study indicate that partially the calculated t value of 4,552 is greater with t table of 2,048, which means that Ho is rejected and Ha is accepted and found the results of the coefficient of determination influence the application of good corporate governance to the quality of financial statements by 42.5%, while the rest of 57.5%, explained by other factors which were not measured in this study. Based on the results of the study it can be concluded that the Implementation of Good Corporate Governance affects the Reliability of Financial Statements. It is better to improve the reliability of financial statements, all parties and units within the company apply the principles of Good Corporate Governance well. Keywords: Good Corporate Governance, Financial Statements, Reliable